Graduate Program in Biomedical Communication - Ryan, Susan M. (1969)
The need for harnessing the achievements of communication technology to the burgeoning mass of biomedical information is critical. Recognizing this problem and aware of the short supply of professionals with the skills necessary for the job, a group of leaders from the fields of medicine and communications formed a consortium in 1967 and have developed a twelve month graduate program in biomedical communication. Designed to ground the advanced student in the development and administration of biomedical communication programs, the curriculum focuses on the principles and practice of communication and the development of communications media. Courses are given in the control and communication of information; the printed and spoken word; visual media of photographic arts, television, and motion pictures; computer science; and administration and systems analysis.